Manajemen Kesiswaan pada Sekolah Dasar Negeri 02 Rantau Alai Kabupaten Ogan Ilir, Sumatera Selatan - Ade Akhmad Saputra; Septi Ayu Enjelina (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
This research aims to describe and analyze the planning, implementation and evaluation of student management at SD Negeri 02 Rantau Alai, Ogan Ilir Regency, South Sumatra. This research uses a descriptive qualitative research design with the school principal as the main research subject. The research focus includes aspects of student program planning, implementation of activities, and the process of evaluating student outcomes. Data was collected through in-depth interviews, direct observation and document analysis. To ensure the validity of the data, this research uses source and method triangulation techniques. The data obtained was analyzed through data reduction, data presentation, and drawing conclusions. The research results show that student management planning includes systematic steps such as new student admissions, student orientation, and class grouping. Implementation of activities is carried out according to established procedures, with a focus on student development individually, socially and academically. Student management evaluations are carried out periodically to assess program effectiveness and provide input for improvement. This research provides a comprehensive picture of the importance of student management as one of the pillars of success in basic education.